A comparative study of Water Control Cultures in China, Japan, and South Korea - Yu Xin; Zhang Zhichao; Liao Chengxi (SHS Web of Conferences, 2023)
The number of World Irrigation Heritage Sites (WHIS), selected by the International Commission on Irrigation and Drainage (ICID), have reached 140 as of 2023, and 83 of them are located in Asia, China, Japan and Korea, which accounts for more than 65% of the total1. This shows that the value of the Eastern Irrigation Project is being recognized worldwide. As an irrigation project, the engineering technology used and the effect of irrigation on the people are one of the most concerned topics, but the spiritual value behind the project are less explored. This paper is based on the investigation and comparison of varied Oriental irrigation heritages of China, Japan and Korea in the register, extracting the common Oriental water control culture of the three countries, and proposing the use of such a culture to help the collaboration around heritage protection in East Asia.